The Lieutenant governor declares he will do nothing in relation to the stamps, but leave it to Sir Henry Moore, to do as he pleases, on his arrival : Council chamber, New-York, Nov. 2, 1765. By order of His Honour Gw. Banyar, d. cl. Con ([publisher not identified], 1765)
Includes a statement by Judge Robert R. Livingston and three others, reporting that the lieutenant goveror had promised not to issue the stamps in Fort-George.